Influence of sports mechanic demands in competitive tennis on the thoracolumbar spinal profile - Dalichau, S.; Scheele, K. (Sportverletzung Sportschaden, 2002)
The aim of this study was to evaluate the influence of the sports mechanic demands of competitive tennis on the thoracolumbar spinal profile. For that reason the spinal curvature (C7 - S2) of 123 male active gymnasts aged 23,8 +/- 4,5 years with a sporting exposure of 14,4 +/- 3,8 years and of 1347 age and gender matched non- and recreational sportsmen was recorded by means of the non-invasive ultrasonic-controlled contact rod. In the sagittal projection no differences between both groups were found. However, in control and sports group the dominant side of the arms induced statistically significant differences for all parameters describing spinal curvature in the frontal and transversal plane, data evaluated showed a relevant increase in the tennis group. Furthermore, the criterion both-handed hitting technique in fore and backhand caused an additional extension of lateral inclination, pelvic and pelvic-shoulder tilt as well as pelvic-shoulder rotation to the hitting side of the arms. After examining the sports-specific mechanic strain the measuring values are to interpret as a functional adaptation to the tennis-specific demands. But there is only a reduced correlation with the results of epidemiologic studies taking the incidence and prevalence of spinal injuries in competitive tennis into special account. So the tennis-specific modifications of spinal profile are not to characterise a priori as pathogen.